Physical exercise and deafness: A integrative review (Research, Society and Development, 2021)
The social inclusion of the deaf is a complex phenomenon that encompasses questions of a moral, conceptual, legal nature, among others. In this way, the main achievement of the deaf was, without a doubt, the officialization of their language as an official Brazilian language, which is a factor of identification, culture and socialization for the deaf. Sport, on the other hand, played a major role in the process of organization and subjective transformation of the deaf, which, in the context of Environmental Education, characterizes it as a tool for modifying the physical and psychosocial environments in which the deaf transit, as it promotes the self-esteem of the deaf. individuals, the autonomy of the groups and the recognition of the others. As sport is a tool for social inclusion, deaf people naturally perceive that there was a great contribution from sports practices in the process of organization and subjective transformation of these individuals. In this context, the Brazilian Confederation of Sports for the Deaf (CBDS) is an institution of immeasurable importance for the deaf in Brazil, but its history is not officially registered, nor is it fully known. For this reason, this study was an integrative, exploratory review of the quantitative and selective type. The Capes, Scielo and google academic databases were used. The relationship between physical exercise and deafness was analyzed, which are the limitations of the deaf in relation to physical activities, which are the difficulties encountered with the inclusion of the deaf in the exercise practices. In practice, there are still many inclusion difficulties, taking into account the lack knowledge of the sign language of professionals who work directly with the deaf. There are still many obstacles to be faced, as inclusion has barriers, and that will only be possible through an awareness of the population.